Environment or genetic isolation? An atypical intestinal microbiota in the Maltese honey bee Apis mellifera spp. ruttneri - Gaggìa, Francesca; Jakobsen, Rasmus Riemer; Alberoni, Daniele; Baffoni, Loredana; Cutajar, Simone; Mifsud, David; Nielsen, Dennis Sandris; Di Gioia, Diana (Frontiers in Microbiology, 2023)
Apis mellifera evolved mainly in African, Asian and European continents over thousands of years, leading to the selection of a considerable number of honey bees subspecies that have adapted to various environments such as hot semi-desert zones and cold temperate zones. With the evolution of honey bee subspecies, it is possible that environmental conditions, food sources and microbial communities typical of the colonised areas have shaped the honey bee gut microbiota. In this study the microbiota of two distinct lineages (mitochondrial haplotypes) of bees Apis mellifera ruttneri (lineage A) and Apis mellifera ligustica and carnica (both lineage C) were compared. Honey bee guts were collected in a dry period in the respective breeding areas (the island of Malta and the regions of Emilia-Romagna and South Tyrol in Italy). Microbial DNA from the honey bee gut was extracted and amplified for the V3-V4 regions of the 16S rRNA gene for bacteria and for ITS2 for fungi. The analyses carried out show that the Maltese lineage A honey bees have a distinctive microbiota when compared to Italian lineage C honey bees, with the most abundant genera being Bartonellaceae and Lactobacillaceae, respectively. Lactobacillaceae in Maltese Lineage A honey bees consist mainly of Apilactobacillus instead of Lactobacillus and Bombilactobacillus in the lineage C. Lineage A honey bee gut microbiota also harbours higher proportions of Arsenophonus, Bombella, Commensalibacter and Pseudomonas when compared to lineage C. The environment seems to be the main driver in the acquisition of these marked differences in the gut microbiota . However, the influence of other factors such as host genetics, seasonality or geography may still play a significant role in the microbiome shaping, in synergy with the environmental aspects.